The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.165
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of negative impact of salts used for winter road maintenance on the environment

Abstract: Winter in Lithuania is the most complicated time of the year to ensure the functioning of transport systems. The main factor which impedes a normal operation of the systems is weather conditions making a direct influence on vehicles and infrastructure elements of transport systems. Precipitation, low air temperature, strong wind and other unfavourable weather conditions impede traffic on the roads and streets. In Lithuania, like in other countries of the world, for the purpose of winter road maintenance (to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…These results are also confirmed in the publication [14] which states that the impacts of chlorides on soil are mainly observable at a distance of approximately 10 m from the body of the road. Another research performed in Lithuania confirmed that the amount of chlorides in ground water within 10 m of a road reached the concentrations of 112-500 mg/L [41].…”
Section: Contamination Of Soil With Chlorides Due To the Application Of De-icing Saltmentioning
confidence: 91%
“…These results are also confirmed in the publication [14] which states that the impacts of chlorides on soil are mainly observable at a distance of approximately 10 m from the body of the road. Another research performed in Lithuania confirmed that the amount of chlorides in ground water within 10 m of a road reached the concentrations of 112-500 mg/L [41].…”
Section: Contamination Of Soil With Chlorides Due To the Application Of De-icing Saltmentioning
confidence: 91%
“…Deicers are frequently detected within 10 m of roadways (Ratkevičius et al, 2014). Road runoff or splash can cause road salts to enter soil, surface waters and groundwater, which can further affect flora, fauna, microbes, and aquatic species (Pecher et al, 2019; Prosser et al, 2017; Ratkevičius et al, 2014).…”
Section: Fate and Transport Of Deicersmentioning
confidence: 99%
“…Deicers are frequently detected within 10 m of roadways (Ratkevičius et al, 2014). Road runoff or splash can cause road salts to enter soil, surface waters and groundwater, which can further affect flora, fauna, microbes, and aquatic species (Pecher et al, 2019; Prosser et al, 2017; Ratkevičius et al, 2014). Composition of the deicer, the amount used, and interaction with other environmental elements are important factors in determining environmental effects of these chemicals (Ratkevičius et al, 2014).…”
Section: Fate and Transport Of Deicersmentioning
confidence: 99%
“…Road salts can enter the roadside environment through a wide variety of pathways, such as runoff, splash and spray from vehicles, or from snow that has been plowed or hauled off site (Zinger and Delisle, 1988;Ramakrishna and Viraraghavan, 2005). Figure 1 outlines the pathways of deicer movement in the environment (Rubin et al, 2010;Ratkevičius et al, 2014). Once applied, deicers can become a part of road runoff or be dispersed aerially.…”
Section: Introductionmentioning
confidence: 99%
“…Once in runoff, they can be part of a surface flow (40-50%) or groundwater transportation (50-60%) and therefore impact soil, flora and fauna. If distributed aerially, deicers can impact the soil, water (mostly surface water), flora, and air quality (Rubin et al, 2010;Ratkevičius et al, 2014;Cheng and Guthrie, 1998;Fischel, 2001 turbidity and bacteria growth, degrading the overall health of streams and making them potentially inhospitable for fish populations. Field research has found that elevated background and spike chloride concentrations in waterways have reduced the richness of amphibian species in some waterways (Turtle, 2000;Houlahan and Findlay, 2003;Collins and Russell, 2009).…”
Section: Introductionmentioning
confidence: 99%